Full-mouth periodontal examination prior to and after nonsurgical treatment in chronic periodontitis patients. - Reis, Cátia (2016)
Chronic periodontitis is a pathological condition characterized by loss of the supporting tissues of the teeth. The aim of this study was to evaluate the distribution of disease sites in different areas of mouth, prior to and following short-term nonsurgical treatment, as well as the successful of treatment. Periodontal parameters, including Probing Pocket Depth (PPD), Clinical Attachment Level (CAL) and Bleeding on Probing (BOP) were recorded in each six surfaces per tooth (mesiobuccal, buccal, distobuccal, mesiolingual, lingual and distolingual), in all mouth teeth of patients with chronic periodontitis, prior to and following nonsurgical periodontal therapy. In total, 374 disease sites (PPD ≥ 4 mm) were found and constituted the sample population of this study. The prevalence of disease sites was higher at mandibular arch, in molars, and at interproximal tooth surfaces, both prior to and after treatment. There was a trend to be more prevalent on the right side of the mouth. Nonsurgical periodontal therapy resulted in a statistically significant decrease in PPD, CAL and in the percentage of BOP sites, even though with a similar pattern of disease distribution after treatment. Following treatment, molars had significantly higher PPD and CAL than other teeth. We conclude that it is important to take particular attention to specific sites in the mouth during management of patients with chronic periodontitis and that short-term nonsurgical treatment is effective in mild/moderate periodontal pockets.